1992
DOI: 10.1007/bf02016264
|View full text |Cite
|
Sign up to set email alerts
|

MRI of sequela of transverse myelitis

Abstract: A 4-year-old boy developed acute paraplegia, associated with sensory impairement and bowel and urinary dysfunction after an URI. MRI showed diffuse hyperintensity in T2WI in the spinal cord below the T6 level. Acute transverse myelitis was diagnosed based on the clinical presentations and MRI findings. The patient had poor recovery and two months later, a follow-up MRI disclosed a severe diffuse atrophic change of the spinal cord in the affected segment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…These findings are consistent with ATM of other causes. Persisting high signal intensity on T2-weighted images and spinal cord atrophy were noted on late MRI of patients with poor outcome [13,30] whereas a reduction in high signal intensity paralleled clinical recovery [1,9,12].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with ATM of other causes. Persisting high signal intensity on T2-weighted images and spinal cord atrophy were noted on late MRI of patients with poor outcome [13,30] whereas a reduction in high signal intensity paralleled clinical recovery [1,9,12].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, cases 2 and 3 showed cord atrophy at 2 months post-onset similar to Shen's case. 6 If spinal cord atrophy appears during the disease course, prognosis will be poor, although one reported case showed no lower-limb deficits despite severe spinal cord atrophy after a cervical operation and postoperative radiotherapy. 7 Nevertheless, spinal cord atrophy must be considered if a pediatric patient with a traumatic or inflammatory spinal cord lesion does not show motor recovery after several months.…”
Section: Spinal Cord Atrophy In the Pediatric Patients Ms Bang And Sjmentioning
confidence: 99%
“…Shen et al 6 reported a case of acute transverse myelitis with cord swelling in the acute stage and diffuse cord atrophy during follow-up MRI at 2 months post-onset. In this study, cases 2 and 3 showed cord atrophy at 2 months post-onset similar to Shen's case.…”
Section: Spinal Cord Atrophy In the Pediatric Patients Ms Bang And Sjmentioning
confidence: 99%
“…Sur les séquences pondérées en T1, un hyposignal peut être vu et peut parfois être rehaussé après injection de gadolinium [8]. À distance peut s'observer une atrophie sévère [9]. La ponction lombaire est habituellement d'une aide précieuse pour le diagnostic de la neurosyphilis.…”
unclassified